2017
DOI: 10.1155/2017/8197085
|View full text |Cite
|
Sign up to set email alerts
|

Endophilin2 Interacts with GluA1 to Mediate AMPA Receptor Endocytosis Induced by Oligomeric Amyloid-β

Abstract: Amyloid-β (Aβ) plays an important role in Alzheimer's disease (AD), as oligomeric Aβ induces loss of postsynaptic AMPA receptors (AMPARs) leading to cognitive deficits. The loss of postsynaptic AMPARs is mediated through the clathrin-dependent endocytosis pathway, in which endophilin2 is one of the important regulatory proteins. Endophilin2, which is enriched in both the pre- and postsynaptic membrane, has previously been reported to be important for recycling of synaptic vesicles at the presynaptic membrane. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…The binding of VGLUT1 to Endophilin recruits the transporter to a fast endocytic pathway and synaptic vesicle recycling, thereby regulating neurotransmitter release and short-term plasticity [88,90]. Endophilin also binds to the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor, either directly to the GluA1, but not GluA2 subunit, or through the adaptor Arc/Arg3.1 [91][92][93] (Table 1). The absence of Arc or Endophilin reduces AMPAR uptake and increases cell surface levels of the receptor, thereby affecting postsynaptic neuron plasticity and long-term depression.…”
Section: Cargoes That May Use Femementioning
confidence: 99%
“…The binding of VGLUT1 to Endophilin recruits the transporter to a fast endocytic pathway and synaptic vesicle recycling, thereby regulating neurotransmitter release and short-term plasticity [88,90]. Endophilin also binds to the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor, either directly to the GluA1, but not GluA2 subunit, or through the adaptor Arc/Arg3.1 [91][92][93] (Table 1). The absence of Arc or Endophilin reduces AMPAR uptake and increases cell surface levels of the receptor, thereby affecting postsynaptic neuron plasticity and long-term depression.…”
Section: Cargoes That May Use Femementioning
confidence: 99%
“…All constructs were verified by sequencing. A detailed description of the methods used for constructing cDNA plasmids is available in previous reports Zhang et al, 2017). Validated spastin siRNA (si-spastin) fragments (5′-CCAGUCAGAUGAGAAAUAUTT-3′) and a negative control (NC; a scrambled sequence) were synthesized by Shanghai GenePharma Co. Ltd. (Shanghai, China).…”
Section: Plasmids and Rna Interferencementioning
confidence: 99%
“…All experiments were repeated independently at least three times. Zhang et al, 2017;Abe et al, 2018). Moreover, our results showed that CRMP2 interacted with endophilin2; hence, we hypothesized that the interaction between CRMP2 and endophilin2 may influence synaptic AMPAR levels.…”
Section: Crmp2 and Endophilin2 Coordinated To Enhance Synaptic Ampar mentioning
confidence: 58%
“…Additionally, our results confirmed that CRMP2 was bound to the SH3 domain of endophilin2 through its C-terminus (Figure 2). In previous studies, endophilin2 has been shown to colocalize with PSD95, suggesting that this protein may be abundantly expressed in postsynaptic regions (Chowdhury et al, 2006;Zhang et al, 2017). Moreover, endophilin2 has also been shown colocalize with GluA1, thereby regulating AMPAR trafficking (Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation